1992
DOI: 10.2134/agronj1992.00021962008400010017x
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Seeding Date for Winter Wheat in Southwestern Saskatchewan

Abstract: Winter wheat (Triticum aestivum L.) in southern Alberta on the Canadian Prairies has traditionally been grown on bare fallow. Recently, the improved winterhardy cultivar Norstar and improved management recommendations, such as seeding directly into stubble or into chemical fallow, have encouraged producers to adapt this crop to the colder climate of southern Saskatchewan. The objective of the experiments reported herein was to determine if the optimum time for seeding winter wheat on stubble and chemical fallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…1c, 1f, and 2i). Overall, these results were consistent with fi ndings from Subedi et al (2007) and McLeod et al (1992), who measured yield reductions up to 40% from late seeding. Th ey also observed that yield losses were exacerbated by low water holding capacity of sandy loam soils, which were similar to soils at the southern location.…”
Section: Grain Yieldsupporting
confidence: 89%
See 1 more Smart Citation
“…1c, 1f, and 2i). Overall, these results were consistent with fi ndings from Subedi et al (2007) and McLeod et al (1992), who measured yield reductions up to 40% from late seeding. Th ey also observed that yield losses were exacerbated by low water holding capacity of sandy loam soils, which were similar to soils at the southern location.…”
Section: Grain Yieldsupporting
confidence: 89%
“…Among the factors that can be controlled by the producer, seeding date is one of the most important because of its impact on productivity (Campbell et al, 1991;McLeod et al, 1992;Sun et al, 2007). Th e choice of seeding date and cultivar might reduce the risk of frost at anthesis, meet vernalization requirements, and favor the accumulation of temperature and precipitation by the plant throughout the growing season.…”
mentioning
confidence: 99%
“…For tlree successive years (1985-1986, 1986_1987, 1987-1988) Seeding was performed with a Swift Current offset zerotill disc drill (Dyck and Tessier 1986) at the optimum time for seeding winter wheat (Fowler 1986;Mcleod et al 1992) (Zadoks et al 1974) by counting the number of surviving plants in five representative l-m sections of row in each plot. Grain (Tables l-3) varied considerably withyear, values-being generally highest in 1987-1988 and lowest in 1985-1986.…”
Section: Methodsmentioning
confidence: 99%
“…Since sowing date is one of the most important management factors affecting crop production and quality [33,34], determinations of appropriate sowing dates for various crops in different regions were documented in some previous literatures (e.g., Chen and Chen [35]; Dennett et al [36]; Olasantan and Bello [37]; Sharma et al [38]). Most of these studies determined the appropriate sowing dates through analyzing the relationship between the sowing date and yields in the years of trial, so these results might be affected by the environmental conditions (e.g., temperature, rainfall) in the trial years.…”
Section: Flexible Sowing Time and Optimal Sowing Timementioning
confidence: 99%